MENGURAI PERMASALAHAN PENDISTRIBUSIAN ZAKAT DENGAN ANALISIS SWOT Studi Kasus Di Lembaga Amil Zakat Daarut Tauhid Solo - Angrahita Grahesti; Ayna Sekar Hutami; Nurulita Novia Sari; Jundiyah Miftahur Rohmah; IIN EMY PRASTIWI (Jurnal Ilmiah Ekonomi Islam, 2023)
The various type of zakat distribution of zakat will not be separated from the constraints or roblems that occur in distributing it. Among the essence of managing zakat trought the amil institution is how to make the zakat distribution program effective which has a positive impact on the welfare of the mustahik himself. This study is aims to analyze or identify problems distribution of zakat at the Amil Zakat Daarut Tauhid Peduli Solo Institute, so that it can be used a qualitative approach with analytical techniques, namely interviews, observation, literature study and SWOT analysis. The result of this study are that there are several problems faced by the Amul Zakat Daarut Tauhid Peduli Solo Institute seen from the aspects of amil/OPZ, muzzaki, mustahik, and regulators which can then be formulated a strategy to unravel these problems trough a SWOT analysis.